2006
DOI: 10.1002/ajmg.a.31186
|View full text |Cite
|
Sign up to set email alerts
|

Fumarase deficiency caused by homozygous P131R mutation and paternal partial isodisomy of chromosome 1

Abstract: We report on the first case of fumarase deficiency (FD) caused by uniparental isodisomy. An affected patient was found to be homozygous for the P131R mutation in the FH gene. In this nonconsanguineous family, the unaffected father was found to be heterozygous for the same mutation, and the mother was found to be homozygous wild-type. Analysis of chromosome 1 markers showed that the patient inherited both paternal alleles with complete absence of the maternal homolog. The two copies of the paternal chromosome 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Previous studies have reported UPD as one of the causes leading to the homozygous mutations in several autosomal recessive disorders [1417]. In fact, UPD involving the LMNA gene was identified in some of the first molecularly characterized patients with HGPS [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported UPD as one of the causes leading to the homozygous mutations in several autosomal recessive disorders [1417]. In fact, UPD involving the LMNA gene was identified in some of the first molecularly characterized patients with HGPS [18].…”
Section: Discussionmentioning
confidence: 99%
“…Fumarase deficiency is a rare inborn error of the metabolism inherited in an autosomal recessive way, with less than 30 unrelated families described to date [Allegri et al, 2010;Bayley et al, 2008;Bonioli et al, 1998;Bourgeron et al, 1994;Coughlin et al, 1998;Deschauer et al, 2006;Gellera et al, 1990;Kerrigan et al, 2000;Loeffen et al, 2005;Manning et al, 2000;Maradin et al, 2006;Phillips et al, 2006;Remes et al, 2004;Whelan et al, 1983;Zeman et al, 2000;Zeng et al, 2006;Zinn et al, 1986], and references therein]. The metabolic disorder is severe, characterized by neurological impairment in early childhood with encephalopathy and seizures, often leading to death in the first years of life.…”
Section: Introductionmentioning
confidence: 97%
“…The metabolic disorder is severe, characterized by neurological impairment in early childhood with encephalopathy and seizures, often leading to death in the first years of life. The diagnosis is suspected on finding elevated fumaric acid levels in urine, and relies on enzymatic assay, which usually shows a residual activity below 10% of control activity in skeletal muscle, lymphocytes, liver tissue or skin fibroblasts (e.g., [Coughlin et al, 1998;Zeng et al, 2006]. Available molecular pathology data for fumarase deficiency did not reveal phenotype-genotype correlations [Bayley et al, 2008].…”
Section: Introductionmentioning
confidence: 98%
“…On the basis of this assumption, anomalies in intermediate metabolites were regarded as secondary phenomena, e.g., high fumaric aciduria in patients. However, genetic studies finally demonstrated that high fumarate excretion in the urine of patients with progressive encephalopathy indeed resulted from primary mutations in the fumarase hydratase (FH)-encoding gene (7,47,65). It was further shown that, far from being restricted to rare cases of encephalopathy, the total loss of FH unexpectedly results in uterine fibroids, skin leiomyomata, and papillary renal cell cancer (58).…”
mentioning
confidence: 99%